Prime Labelings of Snake Graphs - Bigham, Abigail; Donovan, Elizabeth Ann; Pack, James; Turley, Jordan; Wiglesworth, Lesley (The PUMP Journal of Undergraduate Research, 2019)
A prime labeling of a graph G with n vertices is a labeling of the vertices with distinct integers from the set {1, 2 ,..., n} such that the labels of any two adjacent vertices are relatively prime. In this paper, we introduce a snake graph, the fused union of identical cycles, and define a consecutive snake prime labeling for this new family of graphs. We characterize some snake graphs that have a consecutive snake prime labeling and then consider a variation of this labeling.